Differential cross section measurements for ionisation of N2 in coplanar geometry. (17th January 2018) - Sakaamini, Ahmad; Harvey, Matthew; Amami, Sadek; Murray, Andrew James; Madison, Don; Ning, Chuangang
Abstract: Triple differential cross section measurements for ionisation of N2 are presented in a coplanar geometry where one of the outgoing electrons was fixed in angle. Data were obtained at incident electron energies 20 and 40 eV above the ionisation potential for the 3 σ g and 1 π u states, the outgoing electrons carrying equal energies. Six sets of measurements were obtained at each energy, with fixed angles of 45°, 90° and 125° to the incident electron direction. The data are compared to new calculations using distorted wave methods.